Downsized, restructured and greener (2019-23): A new era for China's New Silk Road? - Stephan Barisitz (Oesterreichische Nationalbank (OeNB), 2024)
This study focuses on the most recent development of Chinese overseas investment and construction and of the Belt and Road Initiative (BRI) in 2019-23, from a project-oriented perspective. As a source we use data of the China Global Investment Tracker (CGIT) of the American Enterprise Institute. Overall annual Chinese overseas commitments are found to have peaked in 2017 (at about USD 250 billion), then to have contracted sharply and to have stabilized from 2021 (at around USD 100 billion). A political blowback against Chinese investments in the West (from 2018), the COVID-19 pandemic (from 2020) and the Ukraine war (from 2022) appear to have affected Chinese project expenditure in Western countries more gravely than in Belt and Road partners. Energy, transportation and metals comprised more than two-thirds of commitments in 2019-23. The twelve largest recipients of Chinese investment and construction in these five years were: Indonesia, Saudi Arabia, Singapore, Australia, the UK, Brazil, the US, Iraq, the United Arab Emirates, Russia, Serbia and Malaysia. As of end-2023, almost one-fifth of total commitments (since 2005) had triggered losses and were thus classified as "troubled transactions." In order to adjust exposure against the backdrop of debt problems, average Chinese overseas projects have become smaller in recent years. Moreover, the share of private Chinese investments has increased to 46%, and greenfield outlays have grown to 53% of total overseas commitments, thus eclipsing acquisitions (in 2023). Apart from the Japanese "Partnership for Quality Infrastructure" program launched in 2015, other most recently (2021-2022) established Western rival infrastructure initiatives to the BRI may still require some time to get off the ground.
Keywords: F15; F34; N75; R12; R42; 330; New Silk Road; Belt and Road Initiative; connectivity; infrastructure; transportation; energy; debt trap; troubled transactions; Global South; BRICS+; digital; China; Southeast Asia; Africa; Latin America